2012
DOI: 10.1186/1476-511x-11-147
|View full text |Cite
|
Sign up to set email alerts
|

The role of Odontella aurita, a marine diatom rich in EPA, as a dietary supplement in dyslipidemia, platelet function and oxidative stress in high-fat fed rats

Abstract: BackgroundDietary changes are a major factor in determining cardiovascular risk. n-3 polyunsaturated fatty acids modulate the risk factors for metabolic syndrome via multiple mechanisms, including the regulation of the lipid metabolism. We therefore investigated the effect of Odontella aurita, a microalga rich in EPA, which is already used as a food supplement, on the risk factors for high-fat diet induced metabolic syndrome in rats.MethodsMale Wistar rats were divided into 4 groups and were fed with a standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 53 publications
3
36
0
Order By: Relevance
“…Importantly, the supplementation of HFD with FO has a weaker effect as compared to OA regarding inflammation markers. This difference could be attributed to the composition of OA that contains EPA and other components such as anti-oxidants (Moreau et al 2006, Haimeur et al 2012) that are absent in FO. In conclusion, the originality of our findings is that O. aurita added as whole microalga without any processing or purification to HFD is sufficient to overcome HFD-induced liver insulin resistance and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the supplementation of HFD with FO has a weaker effect as compared to OA regarding inflammation markers. This difference could be attributed to the composition of OA that contains EPA and other components such as anti-oxidants (Moreau et al 2006, Haimeur et al 2012) that are absent in FO. In conclusion, the originality of our findings is that O. aurita added as whole microalga without any processing or purification to HFD is sufficient to overcome HFD-induced liver insulin resistance and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Among marine microalgae, Odontella aurita (O. aurita) presents a high content in eicosapentaenoic acid (EPA) that is a bioactive w-3 FA. Furthermore, the supplementation of diet with O. aurita reduced high fat induced-metabolic syndrome risk including hyperlipidemia and oxidative stress (Haimeur et al 2012). It has been also shown that feeding a rat a high fat diet supplemented with O. aurita increased the level of w-3 FAs content in different tissues such as the liver and platelets.…”
Section: Introductionmentioning
confidence: 94%
“…In this study, the effects of O. aurita as dietary supplement on risk factors linked to metabolic syndrome installation in high fat-fed rats were reported (Haimeur et al, 2012).…”
Section: Effects Of O Aurita Used As Food Supplement On Risk Factomentioning
confidence: 95%
“…ALA, alpha-linolenic acid; EPA, eicosapentaenoic acid; DHA, docosahexaenoic acid. Odontella aurita (Haimeur et al, 2012) In Table 1 are reported the lipid content and the main omega-3 PUFA of interest of microalgae authorized for human nutrition.…”
Section: Microalgae As Lipid and Pufa Sourcesmentioning
confidence: 99%
See 1 more Smart Citation